2010
DOI: 10.1037/a0018535
|View full text |Cite
|
Sign up to set email alerts
|

The p-median model as a tool for clustering psychological data.

Abstract: The p-median clustering model represents a combinatorial approach to partition data sets into disjoint, non-hierarchical groups. Object classes are constructed around exemplars, manifest objects in the data set, with the remaining instances assigned to their closest cluster centers. Effective, state-of-the-art implementations of p-median clustering are virtually unavailable in the popular social and behavioral science statistical software packages. We present p-median clustering, including a detailed descripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 60 publications
0
38
0
1
Order By: Relevance
“…For example, Blanchard, Aloise, and DeSarbo (2012) developed an extension known as the heterogeneous p -median model that is particularly well-suited for applications pertaining to categorization tasks. Moreover, K -median clustering is broadly applicable to very general proximity data, including asymmetric and rectangular dissimilarity matrices (see Köhn et al, 2010). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Blanchard, Aloise, and DeSarbo (2012) developed an extension known as the heterogeneous p -median model that is particularly well-suited for applications pertaining to categorization tasks. Moreover, K -median clustering is broadly applicable to very general proximity data, including asymmetric and rectangular dissimilarity matrices (see Köhn et al, 2010). …”
Section: Resultsmentioning
confidence: 99%
“…By contrast, K -median software is often not commercially available and, instead, must be obtained from other sources. For example, Kaufman and Rousseeuw (2005) offer an R implementation of a K -median heuristic, and Köhn et al (2010) have described a suite of Matlab programs for K -median clustering.…”
Section: Resultsmentioning
confidence: 99%
“…To select an optimal number of clusters, we performed visual analysis of a dendrogram representing the structure of the data and confirmed that we could identify natural groupings using bivariate matrices which provided construct validation. Next, we used the k-medians cluster methodology with a Euclidean distance similarity measure (L2) to verify cluster classifications, for a set number of k clusters ranging from 3–8 (Brusco & Köhn, 2009; Kohn et al, 2010). We used the Calinski pseudo-F statistic, which measures the ratio of between cluster variance to within cluster variance as a quantitative measure of the distinctness of the groups generated by the cluster analysis and provide a stopping rule to optimize the number of groups selected (Calinski & Harabasz, 1974).…”
Section: Methodsmentioning
confidence: 99%
“…It can be applied to cluster metric data as well as to more general similarity/dissimilarity data, even asymmetric or rectangular data structures (i.e., when not every object can be a median) (Köhn et al, 2010). Mladenović et al (2007) present an extensive review of exact and heuristic solution methods for this problem.…”
Section: Introductionmentioning
confidence: 99%